2.45 GHz passive RFID tag antenna mounting on various platforms - Islam, Md. Rafiqul; Abubeker , A. Yussuf; Alam, A. H. M. Zahirul; Ismail, Ahmad Fadzil; Chebil, Jalel; Khan, Sheroz (2011)
This paper presents the design of a passive RFID tag antenna operating at 2.45 GHz. The electromagnetic simulation software called CST is used for design and simulation. A high gain (5.842dB), a good impedance matching with the microchip (-30.0 dB Return Loss) and a satisfactory read range performance (upto 5 m) was obtained. One approach of designing RFID tag is that the tag should be less sensitive to the various types of objects. The effects of obstacles on antenna’s characteristics have been investigated by placing the tag antenna against a metallic, rubber, glass and wood surfaces. Simulation results show slight variations which is within tolerance range.